Instructional Design and Digital Platforms in the Development of Local Wisdom-Based Social Studies Learning Materials: A Systematic Review - Felia Siska; Yenni Melia; Satrio Junaidi; Irwan Irwan; Neffi Sulkasi; Nawalinsi Nawalinsi (International Journal of Social Learning (IJSL), 2025)
The integration of local wisdom into digital learning materials is a strategic approach to strengthening cultural literacy and character education in social studies learning. However, variations in instructional design models and digital platforms have resulted in different levels of pedagogical and cultural effectiveness. This study aims to examine how instructional design models influence the development process and to identify the most effective digital platforms and media for delivering culturally based materials. A Systematic Literature Review (SLR) was conducted using the PRISMA protocol and analyzed through the PICOS framework. The findings reveal that the ADDIE model is most widely implemented due to its flexibility and iterative evaluation process, followed by Borg & Gall, Dick & Carey, and the 4D model, each supporting product validation and pedagogical relevance. Additionally, e-modules and interactive multimedia are the most effective platforms for improving conceptual literacy, while mobile applications and e-learning platforms enhance accessibility and interactivity.